2014
DOI: 10.1111/ijfs.12510
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pulsed electric field processing on carotenoid extractability of carrot purée

Abstract: Summary The purpose of this research was to study the effect of electric field strength (0.1–1 kV cm−1) and frequency (5–75 Hz) during pulsed electric field (PEF) processing on the extractability of carotenoids in carrots, which was examined using different vegetable oils. Increasing electric field strengths up to 1 kV cm−1 at 5 Hz significantly (P < 0.05) increased the extraction of carotenoids from carrot pomace. Increasing frequency above 10 Hz at 1 kV cm−1 did not improve the carotenoids extraction. The yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…The influence of processing on oil soluble vitamins is an additional aspect important for evaluating the adequacy of PEF for industrial applications. The most of the reports documented the effects of PEF on extraction of carotenoids and activity of provitamin A (Roohinejad, Everett, & Oey, ; Roohinejad, Oey, Everett, & Niven, ). Although, both of those can be easily degraded during the production, their retention can be improved with good technological practices.…”
Section: Nutritional Propertiesmentioning
confidence: 99%
“…The influence of processing on oil soluble vitamins is an additional aspect important for evaluating the adequacy of PEF for industrial applications. The most of the reports documented the effects of PEF on extraction of carotenoids and activity of provitamin A (Roohinejad, Everett, & Oey, ; Roohinejad, Oey, Everett, & Niven, ). Although, both of those can be easily degraded during the production, their retention can be improved with good technological practices.…”
Section: Nutritional Propertiesmentioning
confidence: 99%
“…Ohmic‐heated juice thus retained most of the sensory attributes of the initial juice and still reduced microbial and enzymatic activity to required levels. The lower initial heat load during pulsed electric field treatment might induce fewer chemical reactions, resulting in greater retention of the initial flavor compounds (Roohinejad and others ).…”
Section: Food Safety: Preservation By Microbial Inactivation and Hygimentioning
confidence: 99%
“…Likewise, Carbonell-Capella et al [72] observed that after HIPEF processing was applied in a papaya-mango blended beverage, the total carotenoid content was significantly higher than in the untreated sample. This may be due to carotenoids being released or leaching from other minerals or solid substances into the juices as a result of the pulsed electric fields [82]. However, different observations were reported by Morales-de la Peña et al [83] who mentioned that the concentration of total carotenoids in fruit juice-soymilk beverages was significantly diminished (9.8%-18.4%) immediately after HIPEF processing at 35 kV/cm during 800 and 1400 µs.…”
Section: Application Of Non-thermal Technologies In Fruit-based Bevermentioning
confidence: 92%